Les vidéos d'exemples de pratique pour susciter le changement - Florian Meyer
To support the professional development of teachers in Quebec, a web-based professional teacher development application called "Zooming in on Teaching Expertise" was developed. It offers new training strategies based primarily on observation and analysis of videos of practice as well as various tools for promoting reflection on practice.Our aim was to evaluate the effect of a training course entailing examples of practice on video and created within the application. In particular, the study focused on participating elementary school teachers' intentions to modify their practice with respect to the professional competency : "To pilot teaching/learning situations". Using a complex theoretical framework, we confirmed the positive effect, under certain conditions, on teachers' intentions through identifying particular effects on their self-confidence and their ability to validate their own practice.